(untitled) (Vallis Aurea, 2022)
This paper presents a study focusing on parental support in pre-school use of digital technology. The context of the study was home-based English language learning. The aim is to contribute to the understanding of the eff ect of digital technology on English education and family life. The study specifi cally investigated the scope of the indirect parental support during digital technology use to determine whether pre-school children used digital technology such as tablets and smartphones to learn English independently. The study also aimed to determine parents’ attitudes towards the increasing digital technology use by their children. Six parents from Pozega, Pozesko-Slavonska County fi lled in questionnaires and were interviewed regarding the indirect role in supporting their children’s use of smartphones and tablets to learn English. According to previous studies, parents generally considered their support non-existent, however, the fi ndings of these studies indicated that parents provided indirect instructions to their children on how to use digital devices. Present study fi ndings point to signifi cantly less parental support and reinforce the contrary argument – that pre-school children use digital devices and learn English independently.